Evolution of the two-mode entangled states with an atomic coupler - Mahmoud Ahmed, Gharib Subhi; Messikh Azeddine, Azeddine; Hassan, Taher (Institute for Mathematical Research (INSPEM) Universiti Putra Malaysia, 2016)
We develop a model to investigate the behavior of atomic coupler consists of two waveguides, each of which includes a localized or a trapped atom with a two-mode pair coherent state source. The waveguides are placed close enough to each other to allow energy exchange between them. The two atoms, in the different waveguides, are located adjacent to each other. In each waveguide, one mode propagates along and interacts with the atom inside in a standard way as the Jaynes- Cummings model (JCM). The atom-mode system, in each waveguide, interacts with the other one via the evanescent wave. Pair coherent states (PCS) are one of the most important states in quantum information theory since it includes sufficient entanglement causing the violation of the Bell inequality. Moreover, the PCS possesses prominent nonclassical properties such as sub-Poissonian statistics, correlation in the number fluctuations, squeezing and violations of the Cauchy Schwartz inequalities